Pengolahan Limbah Padat Industri Tahu Menjadi Pupuk Kompos - Cory Dian Alfarisi; Ida Zahrina; Elvi Yenie; Silvia Reni Yenti (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Solid organic fertilizer is the result of composting from agricultural waste and livestock waste, which contains macro and micro nutrients so that it can improve soil structure. This study aims to obtain a formula that meets the criteria to be achieved in the manufacture of compost from equalizing sludge in tofu waste with a variety of raw materials such as rice husks and sawdust and to determine the quality of the NPK compost produced with the help of EM4 bioactivator. Compare it with SNI 19-7030-2004. The best composting results were obtained from the raw material composition of 300 grams of tofu solid waste, 350 grams of rice husks, and 350 grams of sawdust with the help of EM4 bioactivator. Composting is carried out for 30 days and the concentration of EM4 in 1 kg of raw material is by mixing 10 ml of EM4 into 1 liter of water. The Nitrogen (N) content was obtained at 1.54%, and the Phosphorus (P) content was obtained at 1.02%, while the Potassium (K) content was obtained at 1.15% and according to SNI 19-7030-2004.